The Influence of the Cooperative Integrated Reading and Composition (CIRC) Learning Model Assisted by Audio-Visual Media on Science Learning Outcomes of Class VII Solar System Material SMPN 8 South Bengkulu - Jannah, Raudhatul; Adisel, Adisel; Hari Mukti, Wiji Aziiz (Universitas Muhammadiyah Sumatera Utara (UMSU), 2024)
This study aims to determine the effect of the Cooperative Integrated ReadingAnd Composition learning model (Circ assisted by audio-visual media) on science learning outcomes for class VII solar system material at SMPN 8 Bengkulu Selatan. This research is a quasi-experimental study with the Non-Equivalent Control Group Design Collection technique. the data in this study was carried out by observation (initial observation), tests and photographs.The data analysis technique used conditional testing and hypothesis testing.The population in this study was class VII, totaling 151 students.The sample of this study used a purposive sampling technique.The data collection method used was a multiple choice test. The data source in this study was taken from pre-test questions and post-test questions with 20 multiple choice questions. The results of the statistical test with the help of SPSS Version 26 showed the value. sig.(2-tailed ) 0.05 or 0.381 0.05. It can be seen that the experimental and control pretests show no significant effect. Based on data analysis using the t-test, it shows that the t-count value = 21.4 and the t-table value = 2.048 So that t-count (2.14) t-table (2.048) with a significance level of 5%. This shows that there is a significant influence of the Cooperative Integrated Reading and Composition (CIRC) learning model assisted by picture story media on the learning outcomes of class VII science.